Pendampingan Pemasaran Digital Untuk Kerajinan Rajut Kepada Ibu-ibu PKK RW V Kelurahan Jomblang Kecamatan Candisari Kota Semarang - Widodo, Sarono; Anif, Muhammad; Wasito, Endro; Wardihani, Eni Dwi; Triyono, eddy; Anggraeni, Sri; Yulianto, Taufiq; Novitasari, Muhlasah (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
Jomblang Village is one of the villages in Candisari sub-district, Semarang city. Jomblang Village has an area of ??± 108 Ha and has a population of 17,322 people, has 15 RWs and 120 RTs. Activities that have been developed in Kelurahan Jomblang include catfish fattening, packaging screen printing, waste processing and catering including tempe craftsmen, tofu into chips. The activity carried out is an initiative of the local community, which is carried out with affordable capital and can be done by residents on the sidelines of free time which can be used as a side job. In this service, PKK mothers in RW V, Jomblang sub-district, Candisari subdistrict, Semarang has conducted training in the form of knitting skills and making simple knitting bags, followed by mentoring on how to market their products digitally (via the internet). The completion of community service is expected to make it easier for mothers to sell their knitting products and increase their product sales to the community through IoT technology so that it can improve the family economy.